2019
DOI: 10.3389/fmars.2019.00265
|View full text |Cite
|
Sign up to set email alerts
|

Managing Recovery Resilience in Coral Reefs Against Climate-Induced Bleaching and Hurricanes: A 15 Year Case Study From Bonaire, Dutch Caribbean

Abstract: Coral reefs are among the world's most endangered ecosystems. Coral mortality can result from ocean warming or other climate-related events such as coral bleaching and intense hurricanes. While resilient coral reefs can recover from these impacts as has been documented in coral reefs throughout the tropical Indo-Pacific, no similar reef-wide recovery has ever been reported for the Caribbean. Climate change-related coral mortality is unavoidable, but local management actions can improve conditions for regrowth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 50 publications
(83 reference statements)
4
58
0
1
Order By: Relevance
“…In a recent Caribbean wide review by Jackson et al (2014) all available coral cover data till 2012 were compiled and for Bonaire results for each research group are also shown in Figure 1 (Figure 6.2 page 185 in the Jackson et al, 2014 report). It is evident from this figure that cover estimates of Steneck and coworkers are quite high compared to the other research groups and again in Steneck et al (2019) they are so high that the authors claim that Bonaire with an average coral cover of ∼47% is actually doing better than the Caribbean maximum measured in the period [1970][1971][1972][1973][1974][1975][1976][1977][1978][1979][1980][1981][1982][1983]. Throughout the manuscript this significant claim is at no point compared to other recent assessments of the Bonaire reef status, even though these coral cover estimates are significantly higher than data for Bonaire collected by us since the 70's (Bak and Nieuwland, 1995;Bak et al, 2005;De Bakker et al, 2016 and other researchers (e.g., Sommer et al, 2011).…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…In a recent Caribbean wide review by Jackson et al (2014) all available coral cover data till 2012 were compiled and for Bonaire results for each research group are also shown in Figure 1 (Figure 6.2 page 185 in the Jackson et al, 2014 report). It is evident from this figure that cover estimates of Steneck and coworkers are quite high compared to the other research groups and again in Steneck et al (2019) they are so high that the authors claim that Bonaire with an average coral cover of ∼47% is actually doing better than the Caribbean maximum measured in the period [1970][1971][1972][1973][1974][1975][1976][1977][1978][1979][1980][1981][1982][1983]. Throughout the manuscript this significant claim is at no point compared to other recent assessments of the Bonaire reef status, even though these coral cover estimates are significantly higher than data for Bonaire collected by us since the 70's (Bak and Nieuwland, 1995;Bak et al, 2005;De Bakker et al, 2016 and other researchers (e.g., Sommer et al, 2011).…”
Section: Introductionmentioning
confidence: 55%
“…A closer look at the methods of Steneck et al (2019) reveals two issues of concern in making comparisons between the authors' estimate of coral cover and other published estimates. First, their method of estimating coral cover differs from conventional methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of natural recovery of Caribbean coral reefs [11] has spurred the need for active management programs to assist in their recovery [12,13]. Management actions include effective spatial planning, enforcement, no take zones, treatment of sewage and protection of adjoining ecosystems such as mangroves [12,[14][15][16]. Resilience-based management of coral reefs [17] may stimulate coral recovery, especially if applied in conjunction with active restoration [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Another avenue is to build ecosystem resilience by further improving conventional management interventions and their governance [6]. Reducing nutrient pollution [24,25], limiting herbivore overfishing [26] and removing coral predators [27] can support resilience by enhancing coral growth and survival. This is so because (i) sediments have direct negative effects on coral recruitment and growth [28,29], and (ii) nutrient run-off in combination with herbivore overfishing reduce coral resilience by favouring the growth and survival of algae which prevent coral recruitment [30,31].…”
Section: Introductionmentioning
confidence: 99%